On Permeability Prediction From Complex Conductivity Measurements Using Polarization Magnitude and Relaxation Time. Issue 5 (16th May 2018) - Robinson, Judith; Slater, Lee; Weller, Andreas; Keating, Kristina; Robinson, Tonian; Rose, Carla; Parker, Beth
Abstract: Geophysical length scales determined from complex conductivity (CC) measurements can be used to estimate permeability k when the electrical formation factor F is known. Two geophysical length scales have been proposed: (1) the specific polarizability c p normalized by the imaginary conductivity σ ″ and (2) the time constant τ multiplied by a diffusion coefficient D + . The parameters c p and D + account for the control of fluid chemistry and/or varying minerology on the geophysical length scale. We evaluated the predictive capability of two CC permeability models: (1) an empirical formulation based on σ ″ or normalized chargeability m n and (2) a mechanistic formulation based on τ . The performance of the CC models was evaluated against measured k ; and further compared against that of well‐established k estimation equations that use geometric length scales. Both CC models predict permeability within one order of magnitude for a database of 58 sandstone samples, with the exception of samples characterized by high pore volume normalized surface area S p o r . Variations in c p and D + likely contribute to the poor model performance for the high S p o r samples, which contain significant dolomite. Two observations favor the implementation of the σ ″ ‐based model over the τ ‐based model for field‐scale k estimation: (1) a limited range of variation in c p relative to D + and (2) σ ″ field measurements are less time consuming to acquire relative to τ . The need for a reliable field‐estimate of F limits application of either model, in particular the σ ″ model due to a high power law exponent associated with F . Key Points: Sandstone permeability is well‐predicted using complex conductivity models except where a high pore volume normalized surface area exists Geophysical length scales used in existing complex conductivity permeability models do not adequately account for variations in minerology Reliable in situ estimates of the electrical formation factor are a critical obstacle to field‐scale implementation of permeability models